Advanced Chemical Sensing Technologies for Environmental Monitoring: Developing High-Sensitivity Sensors for Real-Time Detection of Pollutants, Toxins, and Greenhouse Gases to Combat Climate Change - Ojomo, Tolulope (International Journal of Scientific Research and Management (IJSRM), 2025)
Environmental monitoring has become a critical aspect of global strategies to combat climate change and its far-reaching impacts. Traditional detection methods for pollutants, toxins, and greenhouse gases often lack the precision, sensitivity, and real-time responsiveness required to address the escalating environmental challenges. Advanced chemical sensing technologies have emerged as transformative tools, leveraging innovations in materials science, nanotechnology, and artificial intelligence (AI) to provide high-sensitivity and high-specificity sensors. These sensors are capable of detecting minute concentrations of harmful substances in various environmental settings, including air, water, and soil.This paper provides a comprehensive review of the state-of-the-art in chemical sensing technologies, highlighting their applications in real-time detection of pollutants such as carbon dioxide (CO₂), nitrogen oxides (NOₓ), volatile organic compounds (VOCs), and particulate matter (PM2.5). It examines groundbreaking advancements in sensor materials, such as nanostructured semiconductors, metal-organic frameworks (MOFs), and graphene-based composites, which significantly enhance sensor performance. Furthermore, the integration of AI-driven algorithms into sensor systems is discussed, showcasing their ability to improve detection accuracy, reduce false positives, and process complex environmental data in real-time.Key applications of these sensors include air quality monitoring in urban environments, water quality assessment for the detection of heavy metals, and industrial emissions tracking to ensure regulatory compliance. The paper also addresses the challenges of scalability, sensor durability, and environmental interference, proposing future directions for hybrid systems, energy-efficient designs, and global sensor networks.By exploring the potential of these advanced sensing technologies, this paper emphasizes their pivotal role in mitigating climate change, protecting ecosystems, and supporting sustainable development. Addressing the current limitations and expanding their adoption can significantly enhance environmental monitoring efforts and drive transformative change in combating the climate crisis.